The Reasons of Eurozone Sovereign Debt Crisis and an Empirical Analysis over Permanency of the Crisis - Gulbahar UCLER; Hale KIRMIZIOGLU (International Journal of Economics and Financial Issues, 2014)
This study aims to review how the Eurozone has been formed and to analyze how it has been formed on weak roots, both in public finance and politics. Contrary to economical ideas, political grounds tested the endeavor of creating a powerful the monetary union. Hence, it was very clean to predict upcoming the debt crisis. According to those assumptions known, pre-crisis problems of the countries has been reviewed. Latter, the crisis’ permanency has been tested via PANKPSS if it’s permanent or not? Mainstream acknowledgement on the literature agrees on the crisis is permanent and might lead to dire consequences. Nevertheless, nexus between those countries which has been forged by political bounds cannot be broken by that crisis; thus, the Eurozone might not be break down.